Thin-section Computed Tomography Detects Long-term Pulmonary Sequelae 3 Years after Novel Influenza A Virus-associated Pneumonia - Zhi-Heng Xing; Xin Sun; Long Xu; Qi Wu; Li Li; Xian-Jie Wu; Xu-Guang Shao; Xin-Qian Zhao; Jing-Hua Wang; Long-Yan Ma; Kai Wang (Chinese Medical Journal, 2015)
Background: The aim of this research was to evaluate long-term pulmonary sequelae on paired inspiration-expiration thin-section computed tomography (CT) scans 3 years after influenza A (H1N1) virus-associated pneumonia, and to analyze the affecting factors on pulmonary fibrosis. Methods: Twenty-four patients hospitalized with H1N1 virus-associated pneumonia at our hospital between September 2009 and January 2010 were included. The patients underwent thin-section CT 3 years after recovery. Abnormal pulmonary lesion patterns (ground-glass opacity, consolidation, parenchymal bands, air trapping, and reticulation) and evidence of fibrosis (architectural distortion, traction bronchiectasis, or honeycombing) were evaluated on follow-up thin-section CT. Patients were assigned to Group 1 (with CT evidence of fibrosis) and Group 2 (without CT evidence of fibrosis). Demographics, rate of mechanical ventilation therapy, rate of intensive care unit admission, cumulative prednisolone-equivalent dose, laboratory tests results (maximum levels of alanine aminotransferase, aspartate transaminase [AST], lactate dehydrogenase [LDH], and creatine kinase [CK]), and peak radiographic opacification of 24 patients during the course of their illness in the hospital were compared between two groups. Results: Parenchymal abnormality was present in 17 of 24 (70.8%) patients and fibrosis occurred in 10 of 24 (41.7%) patients. Patients in Group 1 (10/24; 41.7%) had a higher rate of mechanical ventilation therapy (Z = −2.340, P = 0.019), higher number of doses of cumulative prednisolone-equivalent (Z = −2.579, P = 0.010), higher maximum level of laboratory tests results (AST [Z = −2.140, P = 0.032], LDH [Z = −3.227, P = 0.001], and CK [Z = −3.345, P = 0.019]), and higher peak opacification on chest radiographs (Z = −2.743, P = 0.006) than patients in group 2 (14/24; 58.3%). Conclusions: H1N1 virus-associated pneumonia frequently is followed by long-term pulmonary sequelae, including fibrotic changes, in lung parenchyma. Patients who need more steroid therapy, need more mechanical ventilation therapy, had higher laboratory tests results (maximum levels of AST, LDH, and CK), and had higher peak opacification on chest radiographs during treatment are more likely to develop lung fibrosis.